Ghettoes and Diaspora in Classification: Communicating Across the Limits - Olson, Hope A.; Ward, Dennis B. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The Dewey Decimal Classification (DDC) has limitations that reflect the biases of its cultural origins, resulting in problems representing marginalized knowledge domains such as women's studies and feminism. To locate the limits and make them permeable, we adopt theoretical conceptions of space from : Drucilla Cornell's philosophy of the limit, Lorraine Code's rhetorical space, Henri Lefebvre's transparent space, and Gillian Rose's paradoxical spaces. Our project operationalized this. . .